2015
DOI: 10.1016/j.phrs.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

PU-H71: An improvement on nature's solutions to oncogenic Hsp90 addiction

Abstract: Despite recent advances in precision medicine, many molecular-based antineoplastic agents do not potentiate sustainable long term remissions, warranting the investigation of novel therapeutic strategies. Heat shock protein 90 (Hsp90) is a molecular chaperone that not only has oncogenic properties, but also has distinct expression profiles in malignant and normal cells, providing a rational strategy to attain preferential damage. Prior attempts to target Hsp90 with natural product-based compounds have been hamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 152 publications
(224 reference statements)
4
31
0
Order By: Relevance
“…One reason for this dependence is that cancer cells harbor highly active, cancer cell-specific HSP90 that is present in multi-chaperone complexes, which have a markedly higher affinity towards HSP90 inhibitors than uncomplexed HSP90 in normal cells [31, 32]. In addition, cancer cells are frequently addicted to mutated or overexpressed oncoproteins whose proper folding and function is controlled and maintained by HSP90 [15, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this dependence is that cancer cells harbor highly active, cancer cell-specific HSP90 that is present in multi-chaperone complexes, which have a markedly higher affinity towards HSP90 inhibitors than uncomplexed HSP90 in normal cells [31, 32]. In addition, cancer cells are frequently addicted to mutated or overexpressed oncoproteins whose proper folding and function is controlled and maintained by HSP90 [15, 33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, MDR1-overexpressing SW480-R cells show resistance to both PU-H71 and tanespimycin but are sensitive to ganetespib, illustrating that knowledge of MDR1 expression may aid in selecting a specific HSP90 inhibitor. Finally, despite the mixed outcomes of phase 3 clinical trials with MDR1 inhibitors, mostly due to high toxicity in combination with cytotoxic agents, co-administration of PU-H71 and new-generation MDR1 inhibitors may be feasible given the high affinity of PU-H71 for active HSP90 [31, 32] and its specific targeting of complexes comprised of HSP90 and oncogenic fusion proteins in certain cancers [47]. …”
Section: Discussionmentioning
confidence: 99%
“…The most prominent drugs inhibit the ATPase activity of Hsp90 and are based on the geldanamycin, radicicol, or purine derivatives, which function as competitive inhibitors of ATP binding to Hsp90 (Roe et al, 1999; Sidera and Patsavoudi, 2014). Initial geldanamycin and radicicol derivatives proved to be potent inhibitors of Hsp90; however, their therapeutic value is low due to severe toxicity by targeting Hsp90 in normal cells (Jhaveri et al, 2012; Trendowski, 2015). …”
Section: Hsp90mentioning
confidence: 99%
“…In contrast, the Charité Onkologie (CONKO)-004 trial selected patients with advanced pancreatic cancer, a malignancy associated with the highest VTE rates, and demonstrated a clinically significant absolute reduction in VTE risk from 15.1% to 6.4% in control vs treated patients. 9 Although VTE is a relatively rare event, breast cancer is the most common cancer in women worldwide. Thus, the question of whether to use thromboprophylaxis to reduce breast cancer-related VTE has a substantial clinical impact.…”
mentioning
confidence: 99%
“…Tumor cells frequently contain relatively high levels of a "stress active" form of Hsp90 termed TEHsp90, which is required to maintain malignant cell viability and proliferation. Hsp90 inhibitors, including PU-H71, have shown promising preclinical activity in B-cell malignancies; 9 however, cellular responses are typically limited by feedback induction of another chaperone, Hsp70B. CuljkovicKraljacic et al showed that eIF4E was a TEHsp90 client protein in BCL cell lines and that, in turn, eIF4E was required for PU-H71-induced Hsp70B expression.…”
mentioning
confidence: 99%